Pengaruh Penambahan Zat-zat Aditif pada Aktivitas Protease Bacillus megaterium DSM 319 - Sumaryanto Sumaryanto; Deden RW; Mahyudin A. Rahman (Fakultas Farmasi Universitas Pancasila, 2004)
Bacillus megaterium DSM 319 is a microbial neutral protease producer, which is usually used for food and non food (especially for dehairing and bating processes) industries. It was shown in this experiment, that the addition of some additive substances such as sodium benzoat, ammonium quarterner, calcium chloride and zeolite tested as a stabilizer of the ability for protease enzyme activities maintain comparing with control the application for the leather process was sign the difference performance. By using varian analysis and Duncan methode analysis at the 4 additif substances above from 0%, 0.5%, 1%, and 2% can be seen that the highest activity of protease reached at 0.862 U with sodium benzoat and the lowest activity at 0.636 U with zeolite.